Maximalist vs. minimalist shoes: dose-effect response of elastic compression on muscular oscillations - Gellaerts, J.; Pirard, M.; Muzic, J.; Peseux, M.; Ménétrier, A. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The aim of this study was to establish whether maximalist shoes engender fewer muscular oscillations than minimalist shoes and determine to what extent these shoes, when combined with elastic compression (EC), help reduce muscle oscillations. For that purpose, we tested the effects of various levels of compression on the muscular oscillations in maximalist and minimalist footwear.